Protein and the Older Adult - Amanda L. Ford; Wendy J. Dahl (EDIS)
Protein is a nutrient that provides energy for our bodies and is involved in many vital functions, such as repair, maintenance, and immune function. This 3-page document discusses the protein requirements for older adults. Written by Amanda L. Ford and Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, March 2017.